Wybrane tematy związane z kwestią porządku i bezpieczeństwa publicznego na podstawie „Pioniera” i „Słowa Polskiego” z lat 1945-1955 .......... 45 - Gąssowski, Mateusz (Samorząd terytorialny na Dolnym Śląsku: Sprawy, dylematy i wyzwania, 2025)
SELECTED ISSUES RELATED TO PUBLIC ORDER AND SAFETY BASED ON “PIONIER” AND “SŁOWO POLSKIE” (1945-1955)The article analyses selected texts published in the Lower Silesian press between 1945 and 1955 that addressed issues of public safety. The newspapers “Pionier” and “Słowo Polskie” served as the primary source material. The study examines the socio-political aspects of the activities of local government authorities in Lower Silesia during the first decade of post-war Poland. It highlights everyday problems faced by the region’s inhabitants, particularly in relation to housing and crime, as reported through these press outlets.